Manajemen Guru dalam Implementasi Program Keagamaan di SD Istiqomah - Mubarok, Husni; Nortiah, Eni; Kusumastutik, Indah; Ahmad, Azwaliza; Mujiburrohman, Muhammad; Khoirunnisa, Triya (Lembaga Yasin AlSys, 2022)
Teachers are a key to success in education. Teacher management really needs to be considered so that all forms of success are expected to be achieved. Like the existing programs in schools, they can be successful because there is a good teacher management in education. Moving on from that, the writer wants to know how teacher management is in implementing religious programs at Al Istiqomah Elementary School. 2. What are the supporting factors for education management in the implementation of religious programs. At SD Al Istiqomah 3. The toughest obstacle in an education management is in implementing religious programs at SD Al Istiqomah Bandung. In our research, we use a descriptive qualitative approach. namely collecting data based on the factors that support the object of research, then analyze these factors to find the role. Data collection techniques used are interview techniques, observation techniques and documentation study techniques. The data collection techniques used by the researchers in this study consisted of: observation, and documentation. At SDIT Istiqomah Lembang there are several forms of evaluation of activities that are directly related to religious activities including: Each student has a daily control book, daily grade book, grade book report cards, certificates of good conduct. The implementation of the religious activity program at SDIT Istiqomah Lembang is carried out through several activities which are divided as follows: Daily religious program, Monthly religious program, Annual religious activity. Teacher Education Methods at SD Istiqomah 1. Use of interesting learning media in class 2. Tahassus method.